Recommendations for Choosing a Test Dose for Abnormal Toxicity Testing - E. O. Stepanuk; N. P. Neugodova (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Abnormal toxicity testing helps to detect unexpected toxic impurities in medicinal products for parenteral use and in the corresponding active pharmaceutical ingredients of natural origin. In accordance with the requirements of the State Pharmacopoeia of the Russian Federation and in order to obtain reliable results, all test parameters, the most important of which is the test dose, should be correct. In this paper, the experts of the Scientific Centre for Expert Evaluation of Medicinal Products offer their recommendations on range finding. A correct test dose will provide reliable analytical results and ensure the safety of the evaluated medicinal products.